Rare Case of an Intrapericardial Ectopic Thyroid (Struma Cordis) on the Ascending Aorta. (October 2020) - Mesrar, Hicham; Chatel, Didier; Barbey, Christophe; Biny, Jean-Paul; Arnould, Marc-Antoine; Gouffran, Guillaume; Bar, Olivier; Chassaing, Stéphan
Abstract : Supplemental Digital Content is available in the text.